Effect OF nitrogen and potassium on the growth, yield and quality of garlic (Allium sativum) in light textured soils sf Rajasthan* - YADAV, R S; SAMMAURIA, R; RATHORE, M S (The Indian Journal of Agricultural Sciences, 2011)
During the winter seasons of 1998-99, 2000-01 and 2001-02 a field experiment was carried out at Agricultural Research Sration, Mandore, Rajasthan to determine the effect of nitrogen and potassium on growth and yield of garlic (Allium sativum). Maximum and significantly higher bulb yield of garlic was obtained with the combined application of 150 kg of nitrogen and 150 kg of K2O/ha. Application of 100 or 150 kg of nitrogen/ha without potassium was not found significantly superior to 50 kg of nitrogen/ha. Minimum drying of cloves was obtained with 150 kg of K2O/ha, however, this significantly increased with higher doses of nitrogen (100 and 150 kg/ha).